PENGARUH AFILIASI BIG 4, KAP YANG TERDAFTAR DI PCAOB, KEPEMILIKAN MANAJEMEN, DAN JUMLAH KOMITE AUDIT TERHADAP DISCRETIONARY ACCRUALS (Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2006-2010) - , Boria Gemala ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Accruals allow managers to communicate their private and inside information and thereby improve the ability of earnings to reflect underlying economic value. At the same time, managers could abuse the flexibility that permitted by GAAP by engaging an aggressive and opportunistic reporting of accruals which known as earning management. Discretionary accruals is a part of accruals that often used by managers to reflect their opportunistic behavior. This study investigates the effect of Big 4 affiliation, registered public accounting firms on PCAOB, management ownership, and the number of audit committee on the discretionary accruals a common proxy of earning management. Using the listed manufacture company from 2006-2010, this research examines no significant influence between Big 4 affiliation, registered public accounting firms on PCAOB and management ownership on discretionary accruals, but find the number of audit committee had negative influence on discretionary accruals.